Association of Smoking, Obesity, and Psychological Stress with Asthma Severity Among Adult Patients: A Cross-Sectional Study - Harun, Lukman; Mira, Mira; Novendra, Alda; Julianto, Julianto (Journal of Applied Nursing and Health, 2026)
Background: Asthma is a chronic inflammatory airway disease that causes breathing difficulties and affects approximately 12 million people in Indonesia. Smoking status, obesity, and psychological stress have been associated with increased asthma severity and poor outcomes. However, few studies have simultaneously examined the relative influence of these factors on asthma severity among adult patients with asthma in primary healthcare settings. Therefore, this study aimed to analyze the association of smoking status, obesity, and psychological stress with asthma severity. Methods: A quantitative cross-sectional study was conducted among 51 adult asthma patients who had experienced an asthma attack within the previous month and were recruited through purposive sampling. Smoking status was assessed using the Brinkman Index, obesity using Body Mass Index (BMI), psychological stress level using the Perceived Stress Scale (PSS), and asthma severity using clinical classification criteria. Data were analyzed using Spearman’s rank correlation and multivariable ordinal logistic regression, with p < 0.05 considered statistically significant. Results: Among 51 participants, 45.1% had intermittent asthma. Smoking status (r = 0.377, p = 0.006), obesity (r = 0.264, p = 0.041), and psychological stress level (r = 0.375, p = 0.007) were significantly associated with asthma severity. Multivariable ordinal logistic regression revealed that smoking status (aOR = 5.23, 95% CI: 1.35–20.33, p = 0.017) and psychological stress level (aOR = 8.56, 95% CI: 1.64–44.79, p = 0.011) were independently associated with mild persistent asthma compared to those with intermittent asthma. Although obesity contributed significantly to the overall model, its adjusted effect estimates were imprecise and warrant cautious Interpretation. Conclusion: Smoking status and psychological stress were independently associated with asthma severity. Conversely, the association between obesity and asthma severity should be interpreted cautiously because of the imprecise effect estimate and limited statistical power. Of all factors, psychological stress demonstrated the strongest adjusted association with asthma severity.